Rapid analysis of the enterprises’ financial condition as a way of discovery of "bottlenecks" in its activities - Яцюк, С. С. (Scientific Bulletin of Ivano-Frankivsk National Technical University of Oil and Gas (Series: Economics and Management in the Oil and Gas Industry), 2015)
The model of rapid analysis of the company’s financial condition, including the indicators of financial stability, liquidity, profitability, the dynamics of the development and turnover and provides rapid identification of the “bottlenecks” in the enterprise activity. Using the specified model in the practice of LTD “Ivano-Frankivsk Locomotive Repair Plant” activity proved the existence of a threat of crisis and loosing of its solvency in the near future. Also it allowed to identify the main constraints, the removal of which can lead to improving of the company’s majority indexes.